Higher engineering mathematics-III - Rathore, S.K.S (Everest Publishing House, 2011)
Higher engineering mathematics-III / Rathore, S.K.S. -- Pune: Everest Publishing House, 2011 510 R235e6V3 6th ed No. of Copies : 1